Sistem Pendukung Keputusan Penentuan Penerima Bantuan Langsung Tunai (BLT) dengan Kombinasi Metode Clustering K-Means dan Visekriterijumsko Kompromisno Rangiranje (VIKOR) - Reza Ariansyah (ADA Journal of Information System Research, 2024)
Virus Certification of Vaccination Identification by Artificial Intelligence, which is often called the Corona virus, has greatly affected the economy of the world community, especially the economy of the people in Indonesia, for this reason the Indonesian government is taking appropriate steps that are useful for improving the economic problems of the Indonesian people by providing direct cash assistance or often referred to as BLT. . The main goal is to help the economy of communities affected by the impact of the Corona virus. The system for determining direct cash assistance at the Kubah Sentang village office, Pantai Labu District, still uses a simple method. Of course, with this simple system, it is very possible for errors to occur with inaccurate data or direct cash assistance not being on target. The mistake that often occurs is that there are people who do not deserve direct cash assistance but these people receive direct cash assistance. In the decision support system for determining direct cash assistance using the K-Means Clustering method, it is used to partition or divide an object into a cluster subset and the Visekterijumsko Kompromisno Rangiranje (VIKOR) method is useful for getting rankings against the criteria that will be used, as for what happens after using the K-Means Clustering method, the data sample starts with 35 people, with this method grouped into 15 people. Then the Visekterijumsko Kompromisno Rangiranje (VIKOR) method was used for ranking, so from the previous method the data amounted to 15 people. Using the VIKOR method, only 5 people were found who were considered very worthy in determining direct cash assistance (BLT).